2009
DOI: 10.1158/1541-7786.mcr-08-0270
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Genomic Copy Number Profiling of Glioblastoma Multiforme by Single Nucleotide Polymorphism DNA Microarray

Abstract: Glioblastoma multiforme (GBM) is an extremely malignant brain tumor. To identify new genomic alterations in GBM, genomic DNA of tumor tissue/explants from 55 individuals and 6 GBM cell lines were examined using single nucleotide polymorphism DNA microarray (SNP-Chip). Further gene expression analysis relied on an additional 56 GBM samples. SNP-Chip results were validated using several techniques, including quantitative PCR (Q-PCR), nucleotide sequencing, and a combination of Q-PCR and detection of microsatelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 55 publications
5
74
0
3
Order By: Relevance
“…As a first step in prioritizing such putative p53 targets for further study, their potential cancer relevance was determined through examination of various cancer genome data sets. These analyses revealed strikingly frequent focal deletions of chromosome 6q26-27, which includes QKI, in human primary GBM that are present in several of our array-CGH data sets (Maher et al 2006;Wiedemeyer et al 2008;Yin et al 2009). Subsequent analysis of the extensive multidimensional TCGA data sets showed loss of QKI expression in 92 out of 420 (22%) transcriptional profiles, deletion of QKI in 85 out of 420 (20%) array-CGH profiles, and QKI methylation (chromosome 6, base 163,755,107) in 50 out of 250 (20%) methylation profiles; mutation data for QKI have not been completed.…”
Section: Qki Is a Frequently Deleted Tumor Suppressor Gene In Gbmmentioning
confidence: 68%
See 1 more Smart Citation
“…As a first step in prioritizing such putative p53 targets for further study, their potential cancer relevance was determined through examination of various cancer genome data sets. These analyses revealed strikingly frequent focal deletions of chromosome 6q26-27, which includes QKI, in human primary GBM that are present in several of our array-CGH data sets (Maher et al 2006;Wiedemeyer et al 2008;Yin et al 2009). Subsequent analysis of the extensive multidimensional TCGA data sets showed loss of QKI expression in 92 out of 420 (22%) transcriptional profiles, deletion of QKI in 85 out of 420 (20%) array-CGH profiles, and QKI methylation (chromosome 6, base 163,755,107) in 50 out of 250 (20%) methylation profiles; mutation data for QKI have not been completed.…”
Section: Qki Is a Frequently Deleted Tumor Suppressor Gene In Gbmmentioning
confidence: 68%
“…The Cancer Genome Atlas Project (TCGA) (The Cancer Genome Atlas Research Network 2008) has compiled a large collection of highresolution genomic data from clinically annotated tumor samples, providing an unprecedented framework for the rapid discovery of novel cancer genes guided by cancer gene alterations across multiple dimensions of the genome. Here, in the course of conducting a functional genomic screen for p53 targets and mining the TCGA glioblastoma multiforme (GBM) data set and others (Mulholland et al 2006;Wiedemeyer et al 2008;Yin et al 2009), we identified Quaking (QKI) as a potential tumor suppressor gene that is frequently deleted in GBM. The potential importance of QKI in GBM pathogenesis is further elevated by its direct regulation by the TP53 tumor suppressor, the most commonly mutated gene in primary GBM .…”
mentioning
confidence: 99%
“…This hypothesis finds additional support in two prior studies. First, the QKI gene is found on a region of chromosome 6 often deleted in glioblastoma multiforme (51). Additionally, QKI suppresses the growth of colon cancer cells in culture, which is exactly the phenotype we would expect from a splicing factor that enhances the splicing of macroH2A1.1 (50).…”
Section: Discussionmentioning
confidence: 87%
“…5B and C; also see Table S2 at the URL above). Second, two recent reports implicate QKI as a potential tumor suppressor (50,51). Finally, an interaction between QKI and macroH2A1 pre-mRNA was recently reported in a genome-wide screen for site-specific interactions between RNA-binding factors and total RNA called PAR-CLIP (27).…”
Section: ϫ12mentioning
confidence: 97%
“…Importantes vias, como a de p53, possuem anormalidades genéticas em 87% das amostras em GBMs secundários detectadas por microarray de DNA de polimorfismo (SNP-Chip) (Yin et al, 2009). As mutações somáticas de TP53 foram detectadas em 7,4% de GBM analisados, 27,3% em astrocitomas anaplásicos e 43% em astrocitomas de baixo grau em pacientes brasileiros (Uno et al, 2005).…”
Section: Efeito Warburg E Alterações Metabólicas Mitocondriaisunclassified